Human pancreatic tissue dissociation enzymes for islet isolation: Advances and clinical perspectives. Issue 2 (March 2020) - Loganathan, Gopalakrishnan; Balamurugan, Appakalai N.; Venugopal, Subhashree
Abstract: Background and aims: Successful clinical human allo or auto-islet transplantation requires the recovery of a sufficient number of functional islets from either brain-dead or chronic pancreatitis pancreases respectively. Methods: In the last two decades (2000–2019), significant progress has been made in improving the human islet isolation procedures and in standardizing the use of different tissue dissociation enzyme (TDE; a mixture of collagenase and protease enzymes) blends to recover higher islet yields. Results and Conclusions: This review presents information focusing on properties and role of TDE blends during the islet isolation process, particularly emphasizing on the current developments, associated challenges and future perspectives within the field. Highlights: Successful human islet isolation and transplantation indicate importance of intact class 1 collagenase. Recombinant rC1rC2 collagenases have beneficial effects on human islet yield and function. Increasing protease to collagenase dose improves recovery of human islets from young donor pancreases. Low-cost enriched collagenase-purified protease enzyme mixtures for successful human islet isolation.